15th INTERNATIONAL CONFERENCE ON TRANSFORMATION PROCESSES IN SPORT - Cecil J. W. Meulenberg (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2018)
From 12-15th of April 2018 a selection of researchers from the Institute for Kinesiology Research of the Science and Research Centre Koper visited and participated, in the 15th international scientific conference on 'Transformation processes in Sport' organised by the Montenegrin Sports Academy (MSA). The conference entitled 'Sports Performance' was held in coastal Budva. The first lecture session was reduced to two speakers. António Figueiredo of the faculty of Sport Science and Physical Education of the University of Coimbra Portugal, displayed his extensive experience as a football coach and sports advisor into his lecture, 'Youth soccer coaches decisions: There is a biological-related issues bias?'. However, this lecture slightly missed a strong impact, due to the absence of related content supposed to be provided by the intended first speaker Dejan Madic who was going to speak about 'Promotion of exercise interventions in children: Is there a critical period'. Concluding this session was Nejc Šarabon, representing the Faculty of Health Sciences of the University of Primorska, Slovenia with the lecture 'Kinesiology in ergonomics: Focus on back pain', that besides, splendidly introduced the faculty's on-going research projects. Two days of scientific programme were divided into three rooms with parallel sessions, that each hosted oral sessions and poster sessions, of which the topics varied. Ranging amongst others from video games influencing tennis techniques, knee arthroplasty, bed rest influencing skeletal muscle, to movement and assessment in preschool children, and from gender differences in physical activity among elderly and non-physical techniques to counteract functional decline, to, the potential contribution of mussels consumption to a healthier active lifestyle. Through well-moderated sessions the contributors among which students and young researchers, were provided with plenty of time to present their findings, and - time permitting - followed by a fruitful discussion. Several further invited lectures were of interest, especially Remi Radel's of the Université Cote d'Azur, Nice France 'Neurocognitive functions involved in the regulation of effort during endurance exercise: A dual-model perspective', that provided a clear theoretical proposition of the regulatory brain network of physical effort. And the lecture of Boštjan Šimunič of the Science and Research Centre, Koper, Slovenia, dealing with 'Skeletal muscle mechanical contractile properties: From childhood to late adulthood', which showed that through tensiomyography, non-symmetrical development trends in muscle waisting could be observed for subjects that maintain different levels of physical activity. Further detailed information on lectures and posters can be found on MSA's listing of conferences (http://csakademija.me/publications/#book-of-abstracts), where also previous editions can be found. Well worth a browse and a further orientation into developing an interest in this highly diverse and interesting regional conference on sport performance of various disciplines and the like.